If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -12y = 7y + 7 Reorder the terms: 3 + -12y = 7 + 7y Solving 3 + -12y = 7 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 3 + -12y + -7y = 7 + 7y + -7y Combine like terms: -12y + -7y = -19y 3 + -19y = 7 + 7y + -7y Combine like terms: 7y + -7y = 0 3 + -19y = 7 + 0 3 + -19y = 7 Add '-3' to each side of the equation. 3 + -3 + -19y = 7 + -3 Combine like terms: 3 + -3 = 0 0 + -19y = 7 + -3 -19y = 7 + -3 Combine like terms: 7 + -3 = 4 -19y = 4 Divide each side by '-19'. y = -0.2105263158 Simplifying y = -0.2105263158
| 4/5x-48 | | (w^9)^(1/3) | | (-6)+3.98= | | 2x^3+4x^2+4x+8=0 | | 9+9m-4=7m+45-3m | | 6(r-14)+2(r-3)=14 | | 2(3y-7)=2(3+8y) | | 2[2x-1]=18 | | 6(a-14)+5(a-18)=2 | | Y^2-24y+144=-100 | | 2(4*s-16)-5*s=-5 | | 2y=58 | | 95+76=195 | | 4x=7x-1 | | y=4.25x-3 | | 8.1+3.8*h-5.6h=-7.2 | | X(7×10^4)/3=4×10^2 | | j-81=3 | | 9x-4=3x-11 | | 7(2v-1)+2=51 | | 81+21=120 | | 3y^2+11y+9=0 | | 21x=16x-7 | | 4.3*t-2.1*t-2.3=7.6 | | [x-6]=10 | | 12x+2=4x+1 | | (2x+39)=(7x+9) | | 8-3*x=17 | | 5x+3yx=10 | | [-4x]=16 | | 9x^4-25x=0 | | 8-3*x=16 |